ISOLASI DAN UJI AMILOLITIK BAKTERI PENGHASIL AMILASE DARI TANAH TEMPAT PEMBUANGAN AKHIR SAMPAH DI KOTA PADANG - P, Yuswarini Anggun (Pendidikan Biologi, 2014)
Using an amylase of enzyme produced bacteria was used in food industry and non food, in the field of amylasing industry was made bread the manufacture of syrup glucose, the textile industry, detergen industry, and medicine industry . A habitat of bacteria can be found in many areas, such as water, the air, plants, animals, excreta human, warm blooded animals and in the ground.The ground where the final rubbish disposal in padang is habitats that are good to the growth of bacteria pendegradasipati.This research aimed reaching bacteria isolation producing an amylase that the ground where the final disposal of waste picking up in Padang. The study is done from March until June 2014. The sample was taken purposive of sampling, its on characteristic of locations, grassland (T1), the ground of cover (T2), the ground of garbage (T3) and the land of compost (T4 ). While amilolitik test is done in region x of coperties laboratory. The result of this research was obtained different of 23 isolation bacteria but only 13 isolation bacteria that is indicative of the amylase activity. The result of the measure was found 3 isolation bacteria at the greatest in every location there were T2.4,T3.7,and T4.5.